2014
DOI: 10.1111/inr.12090
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of diabetes‐related knowledge among registered nurses working in hospitals in Jordan

Abstract: Promoting continuing education in diabetes for nurses requires continuous effort and creativity. Healthcare system administrators must acknowledge and prioritize the need for this education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 21 publications
8
47
3
1
Order By: Relevance
“…Several studies have been carried out in other countries aimed at ascertaining nurses' knowledge of diabetes and its complications (Scheiderich et al 1983, Drass et al 1989, Burden & Burden 1993, Livingston & Dunning 2010, Yacoub et al 2014, Alotaibi et al 2017. These studies were always carried out on selected groups and sometimes with only few respondents (137 nurses in the study by Scheiderich et al 1983; 184 nurses in the study by Drass et al 1989; 21 nurses in the study by Livingston& Dunning 2010, 277 registered nurses in the study Yacoub et al 2014, 423 nurses in study Alotaibi et al 2017 etc.…”
Section: Diabetes Knowledge Of Nurses In Different Countriesmentioning
confidence: 99%
“…Several studies have been carried out in other countries aimed at ascertaining nurses' knowledge of diabetes and its complications (Scheiderich et al 1983, Drass et al 1989, Burden & Burden 1993, Livingston & Dunning 2010, Yacoub et al 2014, Alotaibi et al 2017. These studies were always carried out on selected groups and sometimes with only few respondents (137 nurses in the study by Scheiderich et al 1983; 184 nurses in the study by Drass et al 1989; 21 nurses in the study by Livingston& Dunning 2010, 277 registered nurses in the study Yacoub et al 2014, 423 nurses in study Alotaibi et al 2017 etc.…”
Section: Diabetes Knowledge Of Nurses In Different Countriesmentioning
confidence: 99%
“…Throughout the world, nurses working in a variety of healthcare settings have been shown to have knowledge deficits in all aspects of diabetes care and its management (Alotaibi, Gholizadeh, Al‐Ganmi, & Perry, ; Gerard, Griffin, & Fitzpatrick, ; Olsen, Granath, Wharén, Blom, & Leksell, ; Yacoub et al., ). A study from Saudi Arabia found that nurses had low accuracy in relation to diet/nutrition, diabetes medications, diabetes pathology, symptoms and management (Alotaibi, Gholizadeh et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A study from Saudi Arabia found that nurses had low accuracy in relation to diet/nutrition, diabetes medications, diabetes pathology, symptoms and management (Alotaibi, Gholizadeh et al., ). They are not unique in this: A Swedish study found that enrolled nurses could not distinguish the different types of diabetes or their symptoms (Olsen et al., ), and inadequate knowledge of diabetes medications was found among nurses in the United States and Jordan (Gerard et al., ; Yacoub et al., ). Nurses indicated that knowledge deficiencies resulted from barriers preventing them achieving full understanding of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate foot care needs a multidisciplinary approach, and nurses play an important role in the prevention, early diagnosis, and caring of DFUs . Therefore, nurses should have up‐to‐date knowledge and know practices about foot care .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Appropriate foot care needs a multidisciplinary approach, and nurses play an important role in the prevention, early diagnosis, and caring of DFUs. 6,7 Therefore, nurses should have up-to-date knowledge and know practices about foot care. 6 A nurse-based foot care program is effective in preventing DFUs, when following evidence-based guidelines.…”
Section: Introductionmentioning
confidence: 99%